Electroencephalographical investigation of drinking green tea to the human brain - Srimanothip, Anjaly; Sittiprapaporn, Phakkharawat (Asian Journal of Medical Sciences, 2020)
Background: Nowadays green tea has become one of the most popular drinks all over the world. Evidences suggest that green tea become second most consumer following regular drinking water. Green tea contains Theanine, an amino acid primarily found in green tea and black tea. The content is generally found 1-2% of dried tea or around 60 milligrams per 200 milliliters of tea drink. In particular, this substance is found in the form of L-theanine that can be absorbed to the blood system and then to the brain within 30 minutes, which causes relaxation and reducing stress. Aims and Objective: The objective was to examine the effect of green tea consumption on electroencephalographic (EEG) activities. Materials and Methods: This study was an experimental design. The participants were twelve Thai healthy, aged between 21-55 years old. During the experiment, all participants were asked to drink green tea every 10 minutes. Results: The influence to brainwave and attentive process were tested by experimental design. The study indicated that alpha brainwave was shown after drinking green tea. Frequency of alpha brainwave along cumulative drinking of green tea was shown significantly since the 10th minute. However, spectrum of the alpha brainwave changed significantly after drinking green tea, after 30th minutes. Conclusion: The benefit of this study was to provide the guideline for planning and campaigning green tea consumption for the purpose of stress reduction resulting in relaxation.